DAILY PORTFOLIO INVESTMENT RETURN ANALYSIS WITH DOLLAR COST AVERAGING METHOD - Arie Himawan (Universitas Trisakti, 2010)
The background of this research was daily investment return strategy with dollar cost averaging method from portfolios which established from day and date of investment in a month. Therefore, it was found that there was highest return from one of those day when investors make investment plans in capital market. The objectives of this research were analyzing best performance day that investors could make most return in a month and along with dollar cost averaging method to avoid rather on risk of single market timing to regular investing. The design of this research applies exploratory research from day and date of investment portfolios which would add market information to investors as reference when make investments as part of their financial plan. Data analysis of this research used Jakarta Composite Index closing price from 2nd Quarter April 2003 to End of March 2008. The results of this research conclude that investors could make high potential investments portfolio return from one of day and date in a month with implementing dollar cost averaging regularly in capital market